Encouraging Teachers to Experience Emodiversity: A Reflective Retelling of a Mental Health Initiative - Mishra, Preeti Vivek (Voices of Teachers and Teacher Educators, 2021)
I was reminded just the other day that I am an emotional educator. This scarcely need a remark, as the majority of educators would concur. What is worth writing about is that I was told this by two distinct education stakeholders (a student and a colleague) in response to somewhat unrelated actions of mine (giving a student who needed both a cup of coffee and a shoulder to weep on, and crying as I recalled a student's academic experience to the aforementioned colleague) and with completely different emotional tones (thank you, and apprehension mixed with disapproval, respectively). I returned from my office that evening in a dazed condition after being reminded by a well-meaning but obviously dissatisfied coworker that I give classes on school mental health.